Simeulue Earthquake Activity Analysis Using the MLE Method - Wattimanela, Henry Junus; Puspito, Nanang Tyasbudi; Batkunde, Harmanus (Faculty of Geography, Universitas Gadjah Mada, 2025)
The territory of Indonesia is prone to a high level of tectonic earthquake vulnerability including In Simeulue Regency, one of the regions of Aceh Province. Therefore, this study aimed to analyze level of tectonic earthquake activity in Simeulue Regency and its surroundings divided into four Sub Regions (I, II, III, and IV). The data used spanned 1940-2020 and were sourced from the ISC with the criteria of the depth being <60km and a magnitude of 3Mw. The seismic features were elucidated through descriptive statistics, while the determination of 'a' and 'b' values for individual Sub Region was accomplished by using the maximum likelihood estimation (MLE) method. The results showed that the highest distribution of earthquakes was at a depth of 15-44.9 km and magnitude at intervals of 3.0-4.9 Mw, specifically in Sub Region III. The largest Mc value was found in Sub Region I, while Sub Region III had high seismic activity and rock heterogeneity. In addition, this area had a large seismicity index and the shortest return period at intervals of magnitude 3.0≤M<4.0. Sub Region I on the other hand had a longer seismicity index at intervals of magnitudes 4.0≤M<5.0,5.0≤M<6.0, and M≥6.0.Received:2023-12-02 Revised:2024-01-11 Accepted:2024-12-07 Published:2025-04-27